Akzeptanz gesellschaftlicher Diversität durch junge Muslim:innen und Christ:innen in Abhängigkeit der Stärke der Religiosität und interreligiöser Kontakte - Zimmer, Veronika (Zeitschrift für Religion, Gesellschaft und Politik, 2022)
Based on a quantitative questionnaire survey (n = 1090) this article provides an overview of the attitudes of young Muslim (13%) and Christian (68%) between 18 and 24 years of age towards diversity operationalized via the acceptance of people of different ethnic and migration backgrounds, religious orientations as well as diverse sexual orientations. The data is analysed in relation to the socio-cultural background (religious affiliation, faith, migration background), socio-economic circumstances (attended schools and educational background of parents) as well as inter-religious and inter-ethnic contacts and friendships. The survey shows that the religious denomination, religiosity and interreligious contacts determine prejudice structures against certain groups, such as homosexuals, to a greater extent than migration background or socioeconomic factors. Positive interreligious and interethnic contacts, especially in the neighbourhood and in friendships have a significant positive influence on diversity acceptance. For example, friendships between native German Christians with young Muslims with migration background are negatively correlated with prejudices against immigrant families. These contacts are also correlated with less prejudices against homosexuals on the side of the young Muslims. In a conclusion, possibilities are discussed to measure and foster diversity acceptance and to support interreligious and intercultural contacts in organizational contexts like in schools in order to initiate positive relationships that help to reduce prejudices.